1976
DOI: 10.1073/pnas.73.6.2106
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid factor and tumor-host interaction.

Abstract: In this survey for rheumatoid factor (RF) seropositivity on patients with neoplasms, an 85% rate of positive screening tests was recorded under certain circumstances. This high rate of RF seropositivity occurred after irradiation and/or chemotherapy of breast and lung cancers. Treated patients with breast cancers who had no evidence of residual tumor had an 89% rate of positive RF tests. Conversely, the incidence of RF seropositivity was low among untreated patients with similar tumors and treated patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In the source population from which our sample was derived, RF was significantly higher in women with ANA antibodies (Supplemental Table S1), but in our sample, this difference was only significant in women who became cases and not in controls (Table 1). We are aware of only one previous study showing elevated RF in breast cancer cases [34]. Further studies are warranted.…”
Section: Discussionmentioning
confidence: 88%
“…In the source population from which our sample was derived, RF was significantly higher in women with ANA antibodies (Supplemental Table S1), but in our sample, this difference was only significant in women who became cases and not in controls (Table 1). We are aware of only one previous study showing elevated RF in breast cancer cases [34]. Further studies are warranted.…”
Section: Discussionmentioning
confidence: 88%
“…Cytotoxic drugs also affect antibody production, and it has been suggested that the effect is particularly marked on T-suppressor-cell function (Diamantstein et al, 1979;Athanassiades et al, 1978). Rheumatoid-factor levels have been shown to rise in patients receiving treatment for breast and bronchial cancer (Twomey et al, 1976) and this may reflect a more generalized disturbance of antibody production leading to increased autoantibody formation and perturbation of idiotypeanti-idiotype interactions. A recent review by Roitt et al (1981) illustrates the complexity of idiotypic networks in control of antibody production and hence the difficulty of predicting the effects of cytotoxic chemotherapy in human disease.…”
Section: Discussionmentioning
confidence: 99%
“…'14This was originally stimulated by the descript-ion of faetors in the serum of tumour-bearing patients and animals which interfere with cell-mediated immunity.5 It has also been suggested that circulating or cell-,bound immune complexes may be responsible for the relatively high frequency of serum antiglobulin responses in cancer patients,6 7 and signs and symptoms of so-called "immune complex disease" may be seen in patients with cancer. 9 More recently it has been suggested that immune complexes cause synthesis and release of prostaglandins and release of lysosomal acid hydrolysases from macrophages.…”
mentioning
confidence: 99%